2006
DOI: 10.1093/ndt/gfi225
|View full text |Cite
|
Sign up to set email alerts
|

Kallikrein/kinin protects against gentamicin-induced nephrotoxicity by inhibition of inflammation and apoptosis

Abstract: This study indicates that kallikrein/kinin protects against gentamicin-induced nephrotoxicity by inhibiting inflammatory cell recruitment and apoptosis through suppression of oxidative stress-mediated signalling pathways. These findings raise the potential of applying kallikrein therapy approaches in treating aminoglycoside-induced renal damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
64
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(76 citation statements)
references
References 18 publications
10
64
0
2
Order By: Relevance
“…This indeed appears to be the case, given that subduing Klk action (using B2 receptor blockers) rendered BALB/c control mice AIGN susceptible, while the administration of BK ameliorated nephritis in AIGN-susceptible 129/SvJ mice ( Figure 3). These findings resonate well with previous genetic and pharmacological studies that also reveal a renoprotective role for Klk and BKs in nephritis following other insults, including hypertension, ischemic stroke, salt imbalance, and diabetes (26)(27)(28)(29)(30)(31)(32)(33)(34)(35). Previous studies suggest that Klk may be playing a protective role in nephritis by modulating several different parameters, including local blood pressure, the inflammatory milieu, redox balance, and/or signaling within various cell types (25,26,31,(36)(37)(38)(39).…”
Section: Figuresupporting
confidence: 89%
See 1 more Smart Citation
“…This indeed appears to be the case, given that subduing Klk action (using B2 receptor blockers) rendered BALB/c control mice AIGN susceptible, while the administration of BK ameliorated nephritis in AIGN-susceptible 129/SvJ mice ( Figure 3). These findings resonate well with previous genetic and pharmacological studies that also reveal a renoprotective role for Klk and BKs in nephritis following other insults, including hypertension, ischemic stroke, salt imbalance, and diabetes (26)(27)(28)(29)(30)(31)(32)(33)(34)(35). Previous studies suggest that Klk may be playing a protective role in nephritis by modulating several different parameters, including local blood pressure, the inflammatory milieu, redox balance, and/or signaling within various cell types (25,26,31,(36)(37)(38)(39).…”
Section: Figuresupporting
confidence: 89%
“…Importantly, this gene complex is encoded within an interval on chromosome 7 that had previously been associated with spontaneous lupus nephritis (14)(15)(16)(17)(18)(19)(20)(21). Kallikreins constitute a multigene family of serine esterases with a wide spectrum of biological functions (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39). These reported functions include the regulation of inflammation, apoptosis, redox balance, and fibrosis within the kidneys, as well as local blood pressure.…”
Section: Figurementioning
confidence: 99%
“…[4][5][6] Accumulating evidence has also suggested that apoptosis, necrosis, and oxidative stress augmentation could be associated with the GM-induced nephrotoxicity. 7,8 Thus, a promising therapeutic approach may be required to curb or protect renal damage against antibiotics adverse effects, and GM-induced nephrotoxicity is an excellent animal model for studying pathogenesis and therapeutic approach development. 9 In the past few years, much attention has been laid on the role of naturally occurring dietary substances for the control and management of various acute and chronic diseases, one such compound berberine has been used since ancient times for promoting human health.…”
Section: Introductionmentioning
confidence: 99%
“…The present study demonstrated that kallikrein/kinin protects against hypertensive renal injury by inhibiting apoptosis in the kidney. Kallikrein/ kinin directly improves renal function, independent of its effects on blood pressure, by inhibiting apoptosis in multiple animal models, including salt-sensitive rats and gentamicininduced renal injury [20,21] . Our previous study demonstrated that rAAV-mediated HK delivery upregulates the B2 receptor and downregulates angiotension II receptor 1, endothelin receptor A and vasopressin receptor 2 [22] , which could also contribute to the anti-apoptotic effects of the kallikrein/kinin system in hypertensive kidney injuries.…”
Section: Discussionmentioning
confidence: 99%